A Pan-Cancer Analysis of the Oncogenic Role of BCL7B: A Potential Biomarker for Prognosis and Immunotherapy - Yang, Dinglong; Li, Hetong; Chen, Yujing; Li, Chunjiang; Ren, Weiping; Huang, Yongbo (Frontiers in Genetics, 2022)
Background: Previous studies have partly explored the role of B-cell CLL/lymphoma 7 protein family member B (BCL7B) in tumorigenesis and development. However, the prognosis and immunoregulatory value of BCL7B in pan-cancer patients remains unclear. Methods: Through the The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) databases, the distinct expression of BCL7B gene in 33 tumors and adjacent normal tissues was analyzed. Kaplan–Meier method (univariate Cox regression analysis and Kaplan–Meier curve) was used to identify the cancer types whose BCL7B gene expression was related to prognosis. The receiver operating characteristic (ROC) curve was used to elucidate the diagnosis value of BCL7B gene. Spearman’s rank correlation coefficient was used to explore the relationship between BCL7B gene expression and immune cell infiltration, immune checkpoints, DNA methylation, DNA repair genes, immune activating genes, immune suppressing genes, immune subtypes, tumor mutation burden (TMB), and microsatellite instability (MSI). Wilcoxon rank sum test and Kuskal Wallis test were used to compare the expression of BCL7B gene in tumor tissues with different clinicalpathologic features. Gene Set Enrichment Analysis (GSEA) was conducted to identify the tumor-related pathways in pan-cancer. Results: High expression of BCL7B was associated with an inferior prognosis in glioblastoma multiforme (GBM), glioma (GBMLGG), kidney chromophobe (KICH), brain lower lrade glioma (LGG), oral squamous cell carcinoma oral squamous cell carcinoma (OSCC), rectum adenocarcinoma (READ), and uveal melanoma (UVM). Low expression of BCL7B was associated with a poor prognosis in kidney renal clear cell carcinoma (KIRC), kidney renal papillary cell carcinoma (KIRP), skin cutaneous melanoma (SKCM), thyroid carcinoma (THCA), and sarcoma (SARC). The BCL7B gene expression had varying degrees of correlation with 24 immune cell subsets in 37 tumor environments such as adrenocortical carcinoma (ACC), and bladder urothelial carcinoma (BCLA). Spearman’s rank correlation coefficient showed that BCL7B gene expression had different degrees of correlation with 47 immune checkpoints, 46 immune activating genes, 24 immune suppressing genes, 5 DNA repair genes, DNA methylation, TMB, and MSI in 39 tumors. Conclusion: In summary, BCL7B gene has a high diagnosis and prognosis value in pan-cancer, and is related to the infiltration of 24 immune cell subsets in pan-cancer.